Membangun Reformasi Birokrasi Berkinerja Dalam Mewujudkan Good Governance Di Kabupaten Gorontalo - Napir, Suaib (Universitas Gorontalo, 2018)
This study aims to analyze, identify and describe strengthening Local Government Organisation Gorontalo District; Methods: Using qualitative research, data collection techniques; observation, interviews and documents. data analysis interactive model of Miles, Hubermen and Saldana (2014). The results showed that: Strengthening the organization, which includes; 1) the incentive has been running with a performance-based; 2) utilization of personnel not comply pd principle the right man on the right pleace; 3) leadership is more motivation in improving individual and organizational performance; 4) organizational culture refers to the Standard Operating Procedure (SOP) that have been standard; 5) communication has been running well, but need to increase understanding of the message to avoid mis communication between SKPD; 6) organizational structure has been carried out by the organization's needs but still dependent on central government policy to discretionary policies at local level walk less than the maximum.